Orbital fat regeneration following hormonal treatment of metastatic breast carcinoma. (4th May 2018) - Alameddine, Ramzi M.; Ko, Audrey C.; Mimura, Masashi; Parker, Barbara A.; Lin, Jonathan H.; Korn, Bobby S.; Kikkawa, Don O.
ABSTRACT: Enophthalmos in the setting of breast cancer metastatic to the orbit results primarily from the disease pathogenesis, or secondary to treatment effects. Orbital volume restoration and fat regeneration following endocrine treatment monotherapy has not been previously reported. A 76- year-old previously healthy female presented with progressive right enophthalmos secondary to metastatic lobular breast carcinoma. Treatment with an aromatase inhibitor (letrozole) resulted in tumor regression and orbital fat restoration with a corresponding improvement in orbital volume and enophthalmos on clinical exam. The patient is alive on continued letrozole with no progressive disease ten years after diagnosis. This case illustrates the resilience of orbital soft tissues and ability of orbital fat to regenerate in face of breast cancer metastasis. We hypothesize that endocrine monotherapy, and avoidance of radiation therapy, allowed for differentiation of remaining orbital stem cells, and facilitated the fat regenerative process.